PENGAJARAN SASTRA DAN PEMBINAAN KARAKTER SISWA - Riska Alfiawati (LPPM STKIP PGRI Bandar Lampung, 2020)
Literature is an imaginative work that is rich in the expression of ideas, ideas, attitudes, and thoughts of the author. Through literature, character building can be done. Literature itself is taught in units of education level. Therefore, character building which includes aspects of students' cognition and emotions. Teaching literature covers three aspects of the realm, both cognitive, affective, and psychomotor. These three domains can be developed to the stage of cognition re-creation, the creation of literary works in response to literature and the application of moral values, culture, ethics, and education. The choice of approach is seen based on the moral development of students in each education unit such as integrated, thematic, and life skills approaches.